Eutectic evolution of directionally solidified Nb-Si based ultrahigh temperature alloys. (February 2018) - Wang, Na; Jia, Lina; Kong, Bin; Guo, Yueling; Zhang, Huarui; Zhang, Hu
Abstract: The purpose of this work is to reveal the eutectic evolution in near-eutectic Nb-Si based alloys. The Nb–xTi–ySi–4Cr–2Al–2Hf (22Ti-15Si; 24Ti-15Si; 22Ti-16.5Si, at.%) alloys were processed by directional solidification with the withdrawal rates of 400 and 500 μm/s. Three typical eutectics were observed: quasi-regular eutectics I, quasi-regular eutectics II and eutectic dendrites colonies. The decrease in the content of Ti and the increase in the withdrawal rate increased the growth rate, and led to the transformation from quasi-regular eutectics I to quasi-regular eutectics II. The increase in the content of Si and the decrease in the withdrawal rate reduced the growth rate, led to larger degree of segregation, and eventually promoted the generation of eutectic dendrites colonies. The sizes of quasi-regular eutectics I and II decreased with the increase in the withdrawal rate and increased with the higher contents of Ti and Si. For the quasi-regular eutectics I and II, the volume fractions of γ-(Nb, Ti)5 Si3 phases increased with increasing the content of Ti. Compared with the quasi-regular eutectics I, more γ-(Nb, Ti)5 Si3 phases existed in the quasi-regular eutectics II, due to the growth pattern transition of the γ-(Nb, Ti)5 Si3 phases. Graphical abstract: Highlights: Three typical eutectics existed in near-eutectic Nb-Si based alloys. Lower content of Ti and larger withdrawal rate promoted the generation of quasi-regular eutectics II. Higher content of Si and lower withdrawal rate caused the generation of eutectic dendrites colonies. Compared with the quasi-regular eutectics I, more γ-(Nb, Ti)5 Si3 phases existed in the quasi-regular eutectics II.